First Report of New Delhi Metallo-β-Lactamase-6 (NDM-6) in a Clinical Acinetobacter baumannii Isolate From Northern Spain - Xanthopoulou, Kyriaki; Urrutikoetxea-Gutiérrez, Mikel; Vidal-Garcia, Matxalen; Diaz de Tuesta del Arco, José-Luis; Sánchez-Urtaza, Sandra; Wille, Julia; Seifert, Harald; Higgins, Paul G.; Gallego, Lucía (Frontiers in Microbiology, 2020)
The objective of this study was the phenotypic and genotypic characterization of a carbapenem resistant Acinetobacter baumannii (CRAB) isolate. The isolate, recovered in Northern Spain in 2019, was identified by MALDI-TOF to the species level. Antimicrobial susceptibility testing was performed using the Phoenix BD NMIC-502 Panel, E-test, and broth microdilution methods. The presence of a metallo-β-lactamase (MBL) was verified by PCR and immunochromatographic assays. The genetic location of the MBL was confirmed using S1-PFGE followed by Southern blot hybridization. Whole genome sequencing (WGS) was completed using the Miseq and MinION platforms, followed by core-genome MLST (cgMLST) and seven-loci MLST analysis. The CRAB was assigned ST85 (Pasteur scheme) and ST957 (Oxford scheme) representing international clone (IC) 9 and harbored the intrinsic β-lactamase OXA-94 with ISAba1 upstream of it, and the MBL blaNDM-6. Hybridization experiments revealed that the blaNDM-6 was encoded on the chromosome. Using WGS the blaNDM-6 environment could be identified arranged in the following order: ISAba14, aphA6, ISAba125, blaNDM-6, bleMBL, trpF, dsbC, cutA and ISAba14. Downstream, a 10,462 bp duplication was identified including a second copy of blaNDM-6 in the following genetic composition: ISAba125, blaNDM-6, bleMBL, trpF, dsbC, cutA and ISAba14. To our knowledge this is the first description of blaNDM-6 in A. baumannii. The MBL was present in two copies in the chromosome in a new genetic environment associated with IS elements highlighting the contribution of mobile genetic elements in the dissemination of this gene.